Influence of the Alternative σ(28) Factor on Virulence and Flagellum Expression of Legionella pneumophila - Heuner, Klaus (American Society for Microbiology, 2002)
The fliA gene of Legionella pneumophila encoding the alternative σ(28) factor was inactivated by introducing a kanamycin resistance cassette. Electron microscopy and Western blot analysis revealed that the fliA mutant strain is aflagellate and expresses no flagellin. Reporter gene assays indicated that the flaA promoter is not active in the fliA mutant strain. The fliA mutant strain multiplied less effectively in coculture with amoebae than the wild-type strain and was not able to replicate in coculture with Dictyostelium discoideum.